Development of an ELISA assay to determine neutralising capacity of horse serum following immunisation with Daboia siamensis venom in Myanmar - Khaing, E; Hurtado, P; Hurtado, E; Zaw, A; White, J; Warrell, D; Alfred, S; Mahmood, M; Peh, C (Elsevier, 2018)
Snakebite envenoming is a serious problem in Myanmar. The great majority of snakebite in this country is due to Russell's Viper (Daboia siamensis). For many years, the Burma Pharmaceutical Industry has produced a monovalent antivenom to Russell's Viper in horses. At present, the only way of determining the level of antibody against D. siamensis venom in hyperimmune horse serum is to perform venom neutralisation tests in mice. In this study, we describe the development of an in vitro ELISA assay to estimate neutralising capacity of horse serum. We found a strong correlation between the ELISA assay and the venom neutralisation test in mice (r = 0.982). The assay is robust and has sufficient sensitivity (92%) and specificity (96%) to replace the venom neutralisation test in mice during the immunisation phase in horses.